Association between Fibromyalgia and Gastrointestinal Comorbidities in a Chinese Population: A Nationwide Cross-Sectional Study - Ullah, Siffat; Zeerak, Laiba; Khan, Izaz; Yasin, Abu Baker Ghulam; Ur-Rahman, Muneeb; Ramzan, Hussain (Archives of Case Reports, 2025)
Objective: Previous studies have indicated a high prevalence of irritable bowel syndrome (IBS) among fibromyalgia (FM) patients. However, data on the association between FM and other gastrointestinal (GI) disorders, particularly in Asian populations, remain limited. This study aimed to investigate the association between FM and both benign and malignant GI disorders in a large Chinese cohort. Methods: We conducted a retrospective cross-sectional study using data from the China Health and Retirement Longitudinal Study (CHARLS). Patients with a documented diagnosis of FM were identified using ICD-10 codes and compared with age- and sex-matched controls. Associations between FM and GI disorders—including IBS, GERD, peptic ulcer disease (PUD), celiac disease, Crohn’s disease, ulcerative colitis, and GI malignancies—were analyzed using logistic regression. Results: A total of 12,450 FM patients and 24,900 matched controls were included. The mean age was 54.2 years (SD = 12.8), and 88% were female. FM was significantly associated with IBS (OR 4.32, 95% CI 3.85–4.85, p < 0.001), GERD (OR 2.45, 95% CI 2.32–2.59, p < 0.001), PUD (OR 2.01, 95% CI 1.86–2.18, p < 0.001), celiac disease (OR 1.92, 95% CI 1.50–2.45, p < 0.001), Crohn’s disease (OR 1.78, 95% CI 1.42–2.24, p < 0.001), and ulcerative colitis (OR 1.69, 95% CI 1.32–2.16, p < 0.001). No significant associations were found between FM and GI malignancies. Conclusion: FM is strongly associated with various benign GI disorders but not with GI malignancies in this Chinese population. These findings highlight the need for integrated care approaches for FM patients with GI symptoms.